Value creation in post-pandemic retailing: a conceptual framework and implications - Monika Imschloss; Martin Schwemmle (Journal of Business Economics, 2023)
In the wake of the Covid-19 pandemic, the retail landscape has undergone profound and enduring changes, necessitating a comprehensive examination of its implications for both consumers and retailers. This study provides a systematic analysis of emergent shifts in consumer behavior and the resulting changes in consumer value creation. The authors develop a conceptual framework encompassing five key dimensions that likely will reshape value creation in post-pandemic retailing: hyperfunctional shopping, holistic health, hybrid connectedness, conscious hedonism, and responsible consumption. The authors propose that consumers will prefer retailers that accomplish creating value based on these dimensions through next-level customer experiences rooted in inspiration and social interaction, novel technologies, and innovations in store concepts, services, or retail operations. Critical to successfully delivering next-level customer experiences in this new retail landscape is retailers' engagement in collaborations—both within the industry and with external partners. Accounting for these developments, this study offers implications for retailing practice and provides a roadmap for future retailing research in five key areas pertaining to the management of responsible, health-related, and digital customer experiences, the management of collaborations for creating next-level customer experiences, and the effective monetization of the evolving dimensions of value creation.
Keywords: L81; M10; M30; O10; 650; Pandemic; Covid-19; Retailing; Value creation; Customer experience; Responsibility